Comparative analysis of thermal decomposition kinetics of carbon dioxide extract from Scabiosa ochroleuca and Scabiosa isetensis at different heating rates - Zhunusova, М.А.; Sarsenbekova, A.Zh.; Abdullabekova, R.M.; Figurinene, I.V. (Ye.A.Buketov Karaganda State University Publ., 2018)
It was presented the analysis of various calculation methods of kinetic parameters of thermal decomposition of СО2-extracts samples that were distilled from Scabiosa ochroleuca and Scabiosa isetensis according to the data of dynamic thermogravimetry. The studies were carried out in air at different heating rates (from 5 to 25 deg/min). Experimental data of TG/DTG/HF methods were processed in accordance with the following kinetic models, namely, Friedman and Flynn-Ozawa-Wall to obtain the kinetic parameters. The use of the above mentioned models makes it possible to determine graphically the effective values of activation energy and pre-exponential factor at different heating rates of the sample and conversion degree. Non-parametric kinetic method was applied (NPK) for objective estimation of complex processes proceeding in parallel with thermal destruction. Non-parametric kinetic method (NPK) is a special approach for processing of kinetic data. Method is a new viewpoint to kinetic analysis, which is based upon rounding of results of single-stage process kinetics. Therefore, simultaneous use of data of TG/DTG/HF methods for kinetic analysis provide us with complete picture of thermal decomposition of carbonic extracts samples obtained from Scabiosa ochroleuca (cream scabious) and Scabiosa isetensis (lomelosia isetensis). In the result section of this study it is proved that the values of kinetic parameters determined by the use of different methods that correspond well with each other.
Scabiosa isetensis жəне Scabiosa ochroleuca СО2-экстракт үлгілерінің əртүрлі жылдамдықта термиялық ыдырауларының салыстырмалы кинетикалық талдауы
Сравнительный анализ кинетики термического разложения образцов углекислотного экстракта из Scabiosa ochroleuca и Scabiosa isetensis при различных скоростях нагрева
Keywords: СО2-extract; Scabiosa ochroleuca; Scabiosa isetensis; thermal analysis; thermal destruction; kinetic parameters; isoconversion method; nonparametric kinetics